LINGUISTIC AND CULTURAL ANALYSIS OF LEXEMES EXPRESSING TRADITION IN ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2024)
In this article we tried to illustrate linguocultural peculiarities and analysis of the lexical units representing Uzbek and English traditions, especially wedding ceremonies and traditions, rituals related to organizing the wedding from beginning to end in both cultures. Tasks of this article is researching the linguistic and cultural features of lexemes representing Uzbek and English wedding ceremonies, clarifying their linguistic and semantic nature to identify their differences and similarities and theoretically analyze them.